Aplikasi E-Modul Berbasis Android Pada Pembelajaran Tematik Kelas 3 Sekolah Dasar - Bagus Nanda Mahardika; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Akademika : Jurnal Teknologi Pendidikan, 2021)
Even though there are still many alternative learning options that teachers can try, books seem to be the main source of learning for students. One of them is with a smart phone or smartphone. Easy access to Android in today's can be used to use it as a teaching medium. There are many media that can be used in today's learning, one of which is the E-module. E-module is a teaching medium that combines technology with learning. The e-module application is one of the solutions that can be implemented for learning today. E-module is also a development of the manual module which is less attractive to students because of its unattractive design. The E-Module application is an android-based application that can be installed on all types of android. Product developed with the ADDIE model. Product Prototype has reviewed by several experts (material, design and media). Some revision has done according to the experts before tested to 58 third grade students of SD Khadijah Pandegiling. The data analysis techniques in this study were qualitative and quantitative. Qualitative data were obtained from suggestions and questionnaire input while quantitative data were obtained from questionnaire percentages.. The evaluation used in this study was a formative evaluation using 2 stages, namely the small group evaluation and the field test. The product trial in small groups was attended by 8 students. The results of the percentage of the small group evaluation or small group evaluation score of 84% or have very good characteristics. Whereas in the large group/ field trial which was attended by 59 students, the percentage was 83%. The main conclusion is this E-modile has increased students reading interest.